Disease Resistance and the Definition of Genetic Enhancement - So, Derek; Kleiderman, Erika; Touré, Seydina B.; Joly, Yann (Frontiers in Genetics, 2017)
Recent gene editing experiments carried out in human embryos have raised the question of whether interventions like the introduction of a CCR5-Δ32 deletion, which could provide heritable resistance to HIV infection, ought to be considered enhancements. Many authors have used the term “enhancement” in different ways, some based on patients’ biomedical outcomes and others on their social context. These classifications are often considered overly imprecise. Nevertheless, the concept of “enhancement” could affect the ways in which these applications are regulated in different jurisdictions, the availability of coverage by insurers or public health care, and the force of public opinion in shaping future policy on gene editing. In order to ethically situate resistance to communicable disease with reference to other techniques, this article provides an overview of its similarities and differences with disease gene therapy in embryos, gene therapy in consenting adults, and vaccination. In discussing key ethical features of CCR5-Δ32 deletion (including its frequency in various populations, biological mechanism, benefits for individuals, and use in previous clinical trials) we offer some potential guideposts for the continuing discussion on how to classify “enhancements” in the age of CRISPR gene editing.